Recurrent Episodes of Acute Pancreatitis Due to Duodenal Gangliocytic Paraganglioma: Report of a Case - Asimakopoulou, Natalia I; Papakonstantinou, Panteleimon E; Lasithiotakis, Konstantinos G; Mouzas, Ioannis A; Daskalogiannaki, Maria E; Tzardi, Maria N; Chalkiadakis, George E (JOP. Journal of the Pancreas, 2014)
Context Gangliocytic paraganglioma is a rare tumor, almost always located in the second portion of the duodenum, and manifested with upper gastrointestinal bleeding and abdominal pain. To date, only one case of duodenal gangliocytic paraganglioma presented with recurrent acute pancreatitis has been reported in the literature. Case report We present a 72-year-old woman admitted to the hospital due to recurrent episodes of acute pancreatitis. Paraclinical examinations showed a polypoid mass in the second portion of duodenum which was removed surgically by local excision. The preoperative differential diagnosis was suggestive with gastrointestinal stromal tumor or adenoma. The histopathology examination revealed a duodenal gangliocytic paraganglioma. After a follow up period of seventeen months the patient remained without clinical evidence of tumor recurrence. Conclusion Our case report draws attention to the need for including in our differential diagnosis of recurrent acute pancreatitis the mechanical obstruction of the pancreatic duct due to this tumor. Image: Proximal view of gangliocytic paraganglioma (Figure 2)